Modeling Traffic Flow on Multi-Lane Road: Effects ofLane-Change Manoeuvres Due to an On-ramp - Ndungu, William Kuria; Kimathi, Mark E. M.; Theuri, David Mwangi (Global Journal of Pure and Applied Mathematics, 2018)
Traffic breakdown is the main cause of vehicle traffic congestion in our multi-lane roads due to highway bottlenecks such as lane-drops, on and off-ramps. In this study the three phase traffic flow theory is outlined and the nature of traffic break down at highway bottlenecks explained. A multi-lane macroscopic traffic flow model of Aw-Rascle type is derived from kinetic traffic flow model which expresses the lane change term explicitly. For simulation of this traffic congestion, we consider a highway with three traffic lanes that has a stationary bottleneck (on-ramp). The model equations for each lane are solved numerically using finite volume method(Godunov scheme), whereby the Euler’s method was used for the source term. The results of simulation near and within the on-ramp is presented in form of graphs and space-time plots. These results indicate that vehicle lane-change manoeuvres lead to heavy traffic breakdown and congestion on the lane adjacent to the bottle neck compared to the other lanes. This is due to the merging of vehicles from on-ramp prompting the following vehicle moving in the adjacent lane to either slow down upon reaching the disturbance region or change to the other lanes before they reachthe merging zone
Keywords: Traffic breakdown; On-ramp; Godunov scheme; Merging zone; Lane-change manoeuvre